Effectiveness and Acceptance of Technology-Based Psychological Interventions for the Acute Treatment of Unipolar Depression: Systematic Review and Meta-analysis - Moritz Köhnen; Levente Kriston; Martin Härter; Harald Baumeister; Sarah Liebherz (JMIR Publications, 2021)
BackgroundEvidence on technology-based psychological interventions (TBIs) for the acute treatment of depression is rapidly growing. Despite extensive research in this field, there is a lack of research determining effectiveness and acceptance of TBIs considering different application formats in people with a formally diagnosed depressive disorder. ObjectiveThe goal of the review was to investigate the effectiveness and acceptance of TBIs in people with diagnosed depression with particular focus on application formats (stand-alone interventions, blended treatments, collaborative and/or stepped care interventions). MethodsStudies investigating adults with diagnosed unipolar depressive disorders receiving any kind of psychotherapeutic treatment delivered (at least partly) by a technical medium and conducted as randomized controlled trials (RCTs) were eligible for inclusion. We searched CENTRAL (Cochrane Central Register of Controlled Trials; August 2020), MEDLINE, PsycINFO, PSYNDEX, CINAHL (January 2018), clinical trial registers, and sources of grey literature (January 2019). Two independent authors decided about study inclusion and extracted data. We performed random effects meta-analyses to synthesize the data. ResultsDatabase searches resulted in 15,546 records of which 78 completed studies were included. TBIs delivered as stand-alone interventions showed positive effects on posttreatment depression severity when compared to treatment as usual (SMD -0.44, 95% CI -0.73 to -0.15, k=10; I²=86%), attention placebo (SMD -0.51, 95% CI -0.73 to -0.30; k=12; I²=66%), and waitlist controls (SMD -1.01, 95% CI -1.23 to -0.79; k=19; I²=73%). Superior long-term effects on depression severity were shown when TBIs were compared to treatment as usual (SMD -0.24, 95% CI -0.41 to -0.07; k=6; I²=48%) attention placebo (SMD -0.23, 95% CI -0.40 to -0.07; k=7; I²=21%) and waitlist controls (SMD -0.74, 95% CI -1.31 to -0.18; k=3; I²=79%). TBIs delivered as blended treatments (providing a TBI as an add-on to face-to-face treatment) yielded beneficial effects on posttreatment depression severity (SMD -0.27, 95% CI -0.48 to -0.05; k=8; I²=53%) compared to face-to-face treatments only. Additionally, TBIs delivered within collaborative care trials were more effective in reducing posttreatment (SMD -0.20, 95% CI -0.36 to -0.04; k=2; I²=0%) and long-term (SMD -0.23, 95% CI -0.39 to -0.07; k=2; I²=0%) depression severity than usual care. Dropout rates did not differ between the intervention and control groups in any comparison (all P≥.09). ConclusionsWe found that TBIs are effective not only when delivered as stand-alone interventions but also when they are delivered as blended treatments or in collaborative care trials for people with diagnosed depression. Our results may be useful to inform routine care, since we focused specifically on different application formats, formally diagnosed patients, and the long-term effectiveness of TBIs. Trial RegistrationPROSPERO International Prospective Register of Systematic Reviews CRD42016050413; https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42016050413 International Registered Report Identifier (IRRID)RR2-10.1136/bmjopen-2018-028042